Efficient anti-corrosive coating of cold-rolled steel in a seawater environment using an oil-based graphene oxide ink. Issue 17 (14th April 2015) - Singhbabu, Y. N.; Sivakumar, B.; Singh, J. K.; Bapari, H.; Pramanick, A. K.; Sahu, Ranjan K.
Abstract : We report the production of an efficient anti-corrosive coating of cold-rolled (CR) steel in a seawater environment (∼3.5 wt% NaCl aqueous solution) using an oil-based graphene oxide ink. Abstract : We report the production of an efficient anti-corrosive coating of cold-rolled (CR) steel in a seawater environment (∼3.5 wt% NaCl aqueous solution) using an oil-based graphene oxide ink. The graphene oxide was produced by heating Aeschynomene aspera plant as a carbon source at 1600 °C in an argon atmosphere. The ink was prepared by cup-milling the mixture of graphene oxide and sunflower oil for 10 min. The coating of ink on the CR steel was made using the dip-coating method, followed by curing at 350 °C for 10 min in air atmosphere. The results of the potentiodynamic polarization show that the corrosion rate of bare CR steel decreases nearly 10 000-fold by the ink coating. Furthermore, the salt spray test results show that the red rusting in the ink-coated CR steel is initiated after 100 h, in contrast to 24 h and 6 h in the case of oil-coated and bare CR steel, respectively. The significant decrease in the corrosion rate by the ink-coating is discussed based on the impermeability of graphene oxide to the corrosive ions.